2020
DOI: 10.1007/s11356-019-07476-x
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of cyanobacteria and microcystins in irrigation water—effects of hydrogen peroxide treatment

Abstract: Cyanobacterial blooms pose a risk to wild and domestic animals as well as humans due to the toxins they may produce. Humans may be subjected to cyanobacterial toxins through many routes, e.g., by consuming contaminated drinking water, fish, and crop plants or through recreational activities. In earlier studies, cyanobacterial cells have been shown to accumulate on leafy plants after spray irrigation with cyanobacteria-containing water, and microcystin (MC) has been detected in the plant root system after irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Although constantly increasing, the number of experiments is limited with exceptional work in natural conditions, and few studies addressed the plants susceptibility to phycotoxins at environmentally relevant concentrations [ 225 , 226 , 228 ]. Despite some crop plants and some aquatic macrophytes (e.g., Ceratophyllum demersum , Elodea canadensis , Phragmites australis , Vesicularia dubyana , and Azolla filiculoides ) having demonstrated possibilities for self-decontamination, for development of tolerance or resistance to cyanotoxins and even registered better growth at certain MC or CYN concentrations, there is a general consensus on the strong negative economic impact with health risk hazards of toxin-containing water, applied as standard or spray irrigation [ 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. Moreover, after conventional treatment, water still can contain extracellular phycotoxins (e.g., MCs), released after lysis of cells [ 236 ].…”
Section: Phycotoxins Of Aero-terrestrial Airborne and Extremophilic Algaementioning
confidence: 99%
See 3 more Smart Citations
“…Although constantly increasing, the number of experiments is limited with exceptional work in natural conditions, and few studies addressed the plants susceptibility to phycotoxins at environmentally relevant concentrations [ 225 , 226 , 228 ]. Despite some crop plants and some aquatic macrophytes (e.g., Ceratophyllum demersum , Elodea canadensis , Phragmites australis , Vesicularia dubyana , and Azolla filiculoides ) having demonstrated possibilities for self-decontamination, for development of tolerance or resistance to cyanotoxins and even registered better growth at certain MC or CYN concentrations, there is a general consensus on the strong negative economic impact with health risk hazards of toxin-containing water, applied as standard or spray irrigation [ 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. Moreover, after conventional treatment, water still can contain extracellular phycotoxins (e.g., MCs), released after lysis of cells [ 236 ].…”
Section: Phycotoxins Of Aero-terrestrial Airborne and Extremophilic Algaementioning
confidence: 99%
“…Despite some crop plants and some aquatic macrophytes (e.g., Ceratophyllum demersum , Elodea canadensis , Phragmites australis , Vesicularia dubyana , and Azolla filiculoides ) having demonstrated possibilities for self-decontamination, for development of tolerance or resistance to cyanotoxins and even registered better growth at certain MC or CYN concentrations, there is a general consensus on the strong negative economic impact with health risk hazards of toxin-containing water, applied as standard or spray irrigation [ 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. Moreover, after conventional treatment, water still can contain extracellular phycotoxins (e.g., MCs), released after lysis of cells [ 236 ]. All studies showed that aquatic macrophytes absorb through all submerged parts [ 229 , 231 ], and crop plants irrigated by infested water can absorb phycotoxins through roots or accumulate it on leaves, and that the effects can be harmful for humans even in cases of no visible changes [ 115 , 225 , 241 ].…”
Section: Phycotoxins Of Aero-terrestrial Airborne and Extremophilic Algaementioning
confidence: 99%
See 2 more Smart Citations
“…These cyanobacteria produce and release a large variety of biologically active secondary metabolites, cyanotoxins (Carmichael, 2001; Zhou, Tu, & Xu, 2015). Microcystins are an environmentally abundant large group of cyclic heptapeptide hepatotoxins (Brózman, Kubickova, & Pavel Babica Petra, 2020; Spoof et al, 2020). there are about 250 microcystin congeners varying primarily in amino acid constitution and degree of methylation (Spoof & Catherine, 2017) among which microcystin LR is widely studied variant (Brózman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%